REPRESENTASI MASKULINITAS GEMALAQ KEMISIQ DALAM KOMIK GEMALAQ KEMISIQ - Dian Nathalia Inda (Balai Bahasa Kalimantan Barat, 2020)
Dayak jalai has some folkflore that has been revitalized in the form of comics. One of those comics about Gemalaq Kemisiq, Kampung Tanjung’s damung. This research will represent about the masculinity of Gemalaq Kemisiq which cointained in the Gemalaq Kemisiq comic and reveal the masculinity of the Gemalaq Kemisiq characters. The method used is a descriptive qualitative method with data collection techniques using literature review. The analysis show that in the Gemalaq Kemisiq comic seen that Gemalaq Kemisiq performs actions and behaviours that represent masculinity while the masculinity traits contained four characteristic namely not using female goods (no sissy stuf), being an important character ( be a big whell), being a person who has strength (be a sturdy oak), and also shows courage (give em hell).